Tourism Revenue Dynamics In The Special Region of Yogyakarta: A Panel Data Analysis - Ainina Ratnadewati; Nur Widiastuti; Ari Sutrichastini; Lilik Ambarwati (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
The tourism sector in the Special Region of Yogyakarta (DIY) is a significant contributor to the Regional Gross Domestic Product (PAD). However, the dynamics occurring before, during, and after the COVID-19 pandemic have created uncertainty regarding the contributions of various factors driving tourism. Empirical knowledge about the variables that most influence tourism revenue remains limited, particularly at the district/city level in DIY. This study aims to analyze the impact of the number of tourists, the number of tourist villages, the number of natural tourist attractions, and the number of museums on tourism revenue in four districts and one municipality in DIY, as well as to identify the factors that play a significant role in shaping the region's tourism performance. This research employs a quantitative approach using panel data analysis covering the period before, during, and after the COVID-19 pandemic. The dependent variable in this study is tourism revenue. In contrast, the independent variables include the number of tourists, the number of tourist villages, the number of natural tourist attractions, and the number of museums. The results indicate that the number of tourist villages (p = 0.0112) and the number of tourists (p = 0.0130) have a positive and significant impact on tourism revenue. Conversely, the number of natural tourist attractions and educational tourism does not show a significant effect. The variable for the number of museums shows a positive influence with a significance value approaching the threshold (p = 0.0527), indicating potential contribution. These findings emphasize that community-based factors and the level of tourist visits are the primary determinants of tourism revenue in DIY. In conclusion, tourism revenue in DIY is more influenced by participatory aspects through tourist villages and the intensity of tourist visits than by the number of formal tourist attractions. Therefore, regional tourism development strategies should focus on strengthening tourist villages and enhancing attractions for visitors